Positive electrode active material for lithium secondary battery, positive electrode for lithium secondary battery and lithium secondary battery

JP2025033086APending Publication Date: 2025-03-13SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023138576
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、サイクル特性に優れるリチウム二次電池を提供できるリチウム二次電池用正極活物質、これを用いたリチウム二次電池用正極及びリチウム二次電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025033086000003
    Figure 2025033086000003
  • Figure 2025033086000004
    Figure 2025033086000004
  • Figure 2025033086000005
    Figure 2025033086000005
Patent Text Reader

Abstract

To provide positive electrode active material for a lithium secondary battery, the positive electrode active material having excellent cycle characteristics of the lithium secondary battery, and to provide a positive electrode for a lithium secondary battery and a lithium secondary battery each being obtained by using the positive electrode active material.SOLUTION: The positive electrode active material for a lithium secondary battery is provided, comprising a lithium metal complex oxide with a layered structure and a compound including one or more elements X selected from P and B. The lithium metal complex oxide includes secondary particles, which are aggregates of primary particles. The compound including the element X is present on the surface of and in the inside of the secondary particles. The positive electrode active material for a lithium secondary battery satisfies (1) and (2).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a positive electrode for a lithium secondary battery, and a lithium secondary battery. [Background technology]

[0002] For the positive electrode constituting the lithium secondary battery, a positive electrode active material for lithium secondary batteries is used. The properties of the positive electrode active material for lithium secondary batteries affect the performance of the lithium secondary batteries, and therefore, active development of positive electrode active materials has been actively carried out with the aim of improving the performance of lithium secondary batteries.

[0003] For example, Patent Document 1 discloses a positive electrode active material for lithium secondary batteries that is coated with a specific metal oxide. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP-A-2019-512450 Summary of the Invention [Problem to be solved by the invention]

[0005] As the range of applications for lithium secondary batteries expands, there is a demand for improved cycle characteristics.

[0006] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a positive electrode active material for a lithium secondary battery that can provide a lithium secondary battery with excellent cycle characteristics, and a positive electrode for a lithium secondary battery and a lithium secondary battery using the same. [Means for solving the problem]

[0007] An aspect of the present invention includes [1] to [8]. A positive electrode active material for a lithium secondary battery, comprising a lithium metal composite oxide having a layered structure and a compound containing at least one element X selected from the group consisting of P and B, wherein the lithium metal composite oxide contains secondary particles which are aggregates of primary particles, the compound containing the element X is present on the surface and inside of the secondary particles, and the positive electrode active material for a lithium secondary battery satisfies the following (1) and (2). 0 < [α / β] ≤ 4.5 (1) 0 atomic% ≤ γ ≤ 9.0 atomic% (2) (In (1), α is the abundance ratio (atomic%) of the element X with respect to all elements on the surface of the positive electrode active material for a lithium secondary battery measured by X-ray photoelectron spectroscopy. β is the content ratio (mol%) of the element X with respect to the total amount of metal elements excluding Li in the positive electrode active material for a lithium secondary battery measured by ICP emission spectroscopy.) (In (2), γ is the abundance ratio (atomic%) of carbon atoms with respect to all elements on the surface of the positive electrode active material for a lithium secondary battery measured by X-ray photoelectron spectroscopy.) [2] The positive electrode active material for a lithium secondary battery according to [1], wherein the positive electrode active material for a lithium secondary battery satisfies the following formula (R). Li:Ni:M:X = (1 + x):y:z:a ··· Formula (R) (In Formula (R), M is at least one element selected from the group consisting of Co, Mn, Fe, Cu, Ti, Mg, Al, W, Mo, Nb, Zn, Sn, Zr, Ga and V, X is the element X, -0.1 ≤ x ≤ 0.2, 0 < y ≤ 0.95, 0 < z ≤ 0.95, 0 < a < 0.05, and y + z + a = 1.) [3] The positive electrode active material for a lithium secondary battery according to [1] or [2], wherein α is greater than 0 atomic% and 5 atomic% or less. [4] The positive electrode active material for a lithium secondary battery according to any one of [1] to [3], which satisfies the following (3). 0 < (α / δ) × 100 ≤ 50 (3) (In (3), δ is the total amount (atomic %) of metal elements other than Li and element X on the surface of the positive electrode active material for a lithium secondary battery, as measured by X-ray photoelectron spectroscopy.) [5] BET specific surface area is 0.1 m 2 / g or more 1.5m 2 / g or less. [6] The positive electrode active material for a lithium secondary battery according to any one of [1] to [5], which has an average crystallite size of 50 nm or more and 150 nm or less. [7] A positive electrode for a lithium secondary battery, comprising the positive electrode active material for a lithium secondary battery according to any one of [1] to [6]. [8] A lithium secondary battery comprising the positive electrode for lithium secondary batteries according to [7]. Effect of the Invention

[0008] According to the present invention, it is possible to provide a positive electrode active material for a lithium secondary battery, which can provide a lithium secondary battery having excellent cycle characteristics, and a positive electrode for a lithium secondary battery and a lithium secondary battery using the same. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram illustrating an example of a lithium secondary battery. [Diagram 2] FIG. 1 is a schematic diagram illustrating an example of an all-solid-state lithium secondary battery. [Figure 3A] FIG. 2 is a cross-sectional photograph of the positive electrode active material for a lithium secondary battery produced in Example 1. [Figure 3B] FIG. 2 is a photograph showing the results of SEM-EDX analysis of a cross section of the positive electrode active material for a lithium secondary battery produced in Example 1. [Figure 4A] 3B is a cross-sectional photograph of FIG. 3A with lines indicated by arrows added thereto. [Figure 4B] This is an element spectrum in the range surrounded by the line indicated by the arrow symbol in FIG. 4A. [Figure 5A] FIG. 4 is a cross-sectional photograph of a positive electrode active material for a lithium secondary battery produced in Comparative Example 3. [Figure 5B] This is an element spectrum in the area surrounded by the dashed line in FIG. 5A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] <Terminology> In this specification, each term is defined as follows. Metal Composite Compound is hereinafter referred to as "MCC." Lithium Metal Composite Oxide is hereinafter referred to as "LiMO." Cathode active material for lithium secondary batteries is hereinafter referred to as "CAM."

[0011] The CAM is an aggregate of a plurality of particles. In one embodiment of the present invention, the CAM is in a powder form.

[0012] LiMO contains secondary particles that are aggregates of primary particles. The LiMO may contain only secondary particles, or may be a mixture of primary and secondary particles.

[0013] The term "primary particles" refers to particles that have no visible grain boundaries when observed at a magnification of 1,000 to 30,000 using a scanning electron microscope or the like. The term "secondary particles" refers to particles in which a plurality of the primary particles are three-dimensionally aggregated with gaps therebetween. In other words, secondary particles are aggregates of primary particles.

[0014] Unless otherwise specified, the notation "Li" indicates elemental Li, not elemental Li metal. The same applies to other elements such as Ni, B, and P.

[0015] For example, when a numerical range is described as "1-10 μm" or "1 to 10 μm," it means a range from 1 μm to 10 μm, including the lower limit of 1 μm and the upper limit of 10 μm.

[0016] [Method of measuring cycle maintenance rate] The cycle characteristics are evaluated in terms of cycle retention, which is measured by subjecting a lithium secondary battery prepared by the following method to the following cycle test.

[0017] (Preparation of positive electrodes for lithium secondary batteries) A paste-like positive electrode mixture is prepared by adding and kneading CAM, a conductive material (acetylene black), and a binder (PVdF) in a ratio of CAM:conductive material:binder = 92:5:3 (mass ratio). When preparing the positive electrode mixture, N-methyl-2-pyrrolidone is used as an organic solvent.

[0018] The obtained positive electrode mixture is applied to a 15 μm thick Al foil as a current collector and dried in vacuum at 150 °C for 8 hours to obtain a positive electrode for a lithium secondary battery. The electrode area of ​​this positive electrode for a lithium secondary battery is 1.65 cm 2 Let us assume that.

[0019] (Production of lithium secondary batteries) The following operations are carried out in a glove box under an argon atmosphere. The above-mentioned positive electrode for lithium secondary battery is placed on the bottom cover of a part for coin-type battery R2032 (manufactured by Hosen Co., Ltd.) with the aluminum foil side facing down, and a laminated film separator (thickness 16 μm) made of a heat-resistant porous layer laminated on a polyethylene porous film is placed on top of it. 300 μl of electrolyte is poured here. The electrolyte is a liquid in which LiPF6 is dissolved at a ratio of 1 mol / l in a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a ratio of 30:35:35 (volume ratio). Next, metallic lithium is used as the negative electrode, which is placed on the top of the separator, and a top lid is placed on the negative electrode via a gasket. The battery is then crimped with a crimping machine to produce a coin-type lithium secondary battery (coin-type half cell R2032).

[0020] (Cycle test) The assembled lithium secondary battery is allowed to stand at room temperature for 12 hours to allow the separator and the positive electrode mixture layer to be sufficiently impregnated with the electrolyte. At a test temperature of 25°C, the charging and discharging currents are set to 0.2 CA, and constant current and constant voltage charging and constant current discharging are performed, respectively. The maximum charging voltage is 4.3 V, and the minimum discharging voltage is 2.5 V. Next, constant current / constant voltage charging and constant current discharging were repeated under the following conditions at a test temperature of 25° C. The charge / discharge cycle was repeated 50 times. Charging: Current setting value 1CA, maximum voltage 4.3V, constant voltage constant current charging Discharge: Battery setting value 1CA, minimum voltage 2.5V, constant current discharge The cycle retention rate is calculated from the discharge capacity at the 1st cycle and the discharge capacity at the 50th cycle using the following formula. The higher the cycle retention rate, the more the battery capacity loss after repeated charging and discharging is suppressed, indicating superior cycle characteristics. Cycle retention rate (%) = 50th cycle discharge capacity (mAh / g) / 1st cycle discharge capacity (mAh / g) × 100 (formula)

[0021] In the CAM in which the amount of Ni relative to the total amount of metal elements excluding Li is 55 mol % or more and less than 80 mol %, and the element X is P, a cycle retention rate of 75% or more under the above measurement conditions is evaluated as excellent in cycle characteristics. In the CAM in which the amount of Ni relative to the total amount of metal elements excluding Li is 55 mol % or more and less than 80 mol %, and the element X is B or P and B, the cycle retention rate under the above measurement conditions is evaluated as excellent in cycle characteristics. In the CAM in which the amount of Ni relative to the total amount of metal elements excluding Li is 80 mol % or more and the element X is P, B, or P and B, the cycle retention rate under the above measurement conditions is evaluated as excellent in cycle characteristics.

[0022] <Positive electrode active material for lithium secondary batteries> The CAM comprises a compound containing LiMO having a layered structure and one or more elements X selected from the group consisting of P and B. Compounds containing element X are present on the surface and inside the secondary particles of LiMO.

[0023] In this specification, the "surface" of a secondary particle means the range from the outermost surface of the secondary particle to the depth at which photoelectrons can escape toward the center of the secondary particle in measurement by X-ray photoelectron spectroscopy described later, for example, the range of depth within about 10 nm from the outermost surface of the secondary particle toward the center of the particle. The "outermost surface of a secondary particle" means the outer shell part on the outermost surface side of the secondary particle.

[0024] In this specification, the "inside" of a secondary particle means a region closer to the center of the particle than the "surface of the secondary particle" defined above. For example, it means a region from a position about 10 nm deep from the outermost surface of the secondary particle toward the center of the particle to the center of the particle. For example, this region includes the interface between primary particles, the inside of the primary particle, and the gap between aggregated primary particles.

[0025] A non-aqueous electrolyte that constitutes a lithium secondary battery (for example, a non-aqueous electrolyte containing LiPF6 as a solute) may be oxidatively decomposed during charging, generating an acid (for example, hydrogen fluoride). When the acid produced reacts with the residual lithium components, water is produced as a by-product. The residual lithium components are lithium compounds (e.g., lithium hydroxide) that remain unreacted during the production of CAM, or lithium compounds (e.g., lithium carbonate) that are produced by a side reaction with components in the air. The by-product water decomposes the electrolyte (e.g., LiPF6) in the electrolyte, degrading the electrolyte.

[0026] For example, when lithium hydroxide reacts with hydrogen fluoride, water is produced as a by-product through the following reaction: LiOH+HF→LiF+H2O

[0027] For example, when lithium carbonate reacts with hydrogen fluoride, water is produced as a by-product through the following reaction: Li2CO3+2HF→2LiF+H2O+CO2

[0028] The compound containing element X contained in CAM reacts with the generated hydrogen fluoride, making it possible to remove the hydrogen fluoride without producing water as a by-product. When the compound containing element X is lithium phosphate, hydrogen fluoride is decomposed according to the following reaction: Li3PO4+HF→LiF+Li2HPO4 When the compound containing element X is lithium borate, hydrogen fluoride is decomposed according to the following reaction: Li3BO3+HF→LiF+Li2HBO3

[0029] A CAM having a compound containing element X on the surface of a secondary particle of LiMO can decompose hydrogen fluoride on the surface of the secondary particle without producing water as a by-product. On the other hand, when the CAM is pressed during the manufacture of a lithium secondary battery, or when the lithium secondary battery is in operation with repeated charging and discharging, the CAM particles may crack and new surfaces may be generated inside the secondary particles. The new surfaces are prone to oxidative decomposition reactions of the electrolyte. In contrast, the above-mentioned CAM has a compound containing element X inside the secondary particles of LiMO, so that hydrogen fluoride can be decomposed without producing water as a by-product, even on the new surfaces generated inside the particles.

[0030] That is, by providing a compound containing element X on the surface and inside of secondary particles of LiMO, CAM can effectively remove hydrogen fluoride, which causes deterioration of electrolyte in various situations, without producing water as a by-product. Therefore, it is possible to provide a lithium secondary battery with excellent cycle characteristics, in which the capacity is not easily reduced when charging and discharging are repeated.

[0031] In this embodiment, whether or not a compound containing element X is present inside the secondary particle can be confirmed by observing a cross section of the secondary particle using a scanning electron microscope-energy dispersive X-ray spectroscopy.

[0032] In this embodiment, "scanning electron microscope-energy dispersive X-ray spectroscopy" is abbreviated as "SEM-EDX."

[0033] In CAM, a compound containing element X is present inside a cross section of a secondary particle observed by SEM-EDX, that is, in a region closer to the center of the particle than the "surface of the secondary particle" defined above.

[0034] The element X may be present as a solid solution on the surface of the primary particles constituting the secondary particles, or may be present as aggregates in the gaps between the primary particles or in the grain boundaries.

[0035] [Analysis of secondary particle cross sections] The cross section of the secondary particle can be obtained by the following method.

[0036] (How to obtain a cross section) In this specification, the "cross section" of a secondary particle is prepared by the following method. First, CAM particles are dispersed in a resin for fixing particles. Then, the mixture is vacuum degassed, and the resulting product is sandwiched between aluminum plates and cured. This results in a cured resin containing particles. The cured product is fixed to a sample stage and set in a cross section specimen preparation device. The cross section specimen preparation device is also called a cross section polisher, and for example, JEOL's IB-19520CCP can be used. The cross section of the secondary particle is prepared by argon ion beam processing at an ion acceleration voltage of 6.0 kV.

[0037] As an SEM-EDX device, for example, a Schottky field emission scanning electron microscope (manufactured by JEOL Ltd., product name JSM-7900F) equipped with an Oxford Instruments X-Max 150 as an EDX detector can be used. The cross section of the secondary particles obtained above is observed using an SEM and elementally analyzed by EDX. The secondary particles observed at this time have a 50% cumulative volumetric particle size D 50 It is preferable to select secondary particles that exhibit a maximum diameter of (μm) ±5%.

[0038] "A compound containing element X is present inside a secondary particle" means that element X is detected inside the cross section when the presence of elements in the cross section is analyzed by SEM-EDX. The presence of element X may be confirmed from element mapping data obtained by SEM-EDX, or from spectrum data.

[0039] [Compound containing element X] The compound containing the element X has lithium ion conductivity. The element X may be either P or B, or may be both.

[0040] The compound containing the element X includes an inorganic compound containing the element X. The compound containing the element X is preferably an oxide containing the element X, and more preferably an oxide containing the element X and Li. The presence or absence of Li in the compound containing the element X can be confirmed, for example, by performing XAFS measurement. Compounds containing P as the element X are lithium phosphate (Li3PO4), lithium metaphosphate (LiPO3), lithium dihydrogen phosphate (LiH2PO4), lithium dihydrogen phosphate (Li2HPO4), lithium pyrophosphate (Li4P2O7), Li4P2O6, and Li5P3O. 10 , Li6P4O 14 etc. Compounds containing B as the element X include lithium borate (Li2B4O7), lithium triborate (Li3BO3), and lithium metaborate (LiBO2).

[0041] The CAM satisfies the following (1) and (2). In this specification, "all elements" refers to all elements contained in the CAM that can be detected by X-ray photoelectron spectroscopy, including oxygen atoms and carbon atoms. "Metal elements other than Li" refers to metal elements that can be detected by ICP emission spectroscopy, including, for example, Ni and the element M described below, and does not include Li, non-metal element X, carbon atoms, oxygen atoms, etc. 0<[α / β]≦4.5 (1) 0atomic%≦γ≦9.0atomic% (2) In (1), α is the abundance ratio (atomic %) of element X to all elements on the surface of the CAM measured by X-ray photoelectron spectroscopy, and β is the content ratio (mol %) of element X to the total amount of metal elements excluding Li on the CAM measured by ICP emission spectroscopy. In (2), γ is the proportion (atomic %) of carbon atoms to all elements on the surface of the CAM, as measured by X-ray photoelectron spectroscopy.

[0042] α / β is the ratio of element X present on the surface of the CAM to the total amount of element X contained in the CAM, and indicates the degree to which element X is unevenly present on the surface of the CAM. For example, when α / β=0, it means that element X is not present on the surface of the CAM, and when 4.5<[α / β], it means that element X is excessively present on the surface of the CAM compared to the interior. γ indicates the proportion of carbon atoms originating from components that become the source of resistance or hydrogen fluoride generation.

[0043] [Method of measuring α, γ, and δ] The above-mentioned "X-ray photoelectron spectroscopy" is referred to as "XPS." With XPS, the constituent elements of the CAM surface can be analyzed by measuring the energy of photoelectrons generated when the surface of a CAM particle is irradiated with X-rays.

[0044] The "surface of the CAM" where the constituent elements are analyzed by XPS refers to the outermost surface of the CAM particle and the depth region where photoelectrons generated from the outermost surface toward the center of the particle can escape. This depth region refers to a region up to a depth of about 10 nm, for example.

[0045] The binding energy of photoelectrons emitted from the surface of CAM when irradiated with AlKα X-rays as the excitation X-ray is analyzed. XPS can analyze α, γ, and δ, which will be described later.

[0046] [X-ray photoelectron spectroscopy] As the X-ray photoelectron spectrometer, for example, PHI5000 VersaProbe III manufactured by ULVAC-PHI, Inc. can be used. The measurement conditions are as follows: X-ray source = AlKα ray (1486.6 eV), X-ray spot diameter = 100 μm, PassEnergy = 112 eV, Step = 0.1 eV, Dwell time = 50 ms, neutralization gun = current 100 μA. The acceleration voltage is adjusted according to the element type. The number of each element is calculated from the peak area of ​​each element using analysis software (MultiPak (Version 9.9.0.8)) for the obtained XPS spectrum. A few mg of CAM powder is used for the measurement. In addition, charging correction is performed with the C1s peak at 284.6 eV.

[0047] Next, from the calculated number of each element, α (unit: atomic %), which is the ratio of the number of element X to the total number of each element (100 atomic %), is calculated.

[0048] Similarly, from the calculated number of each element, γ (unit: atomic %), which is the ratio of the number of carbon atoms to the total number of each element (100 atomic %), is calculated.

[0049] In addition, from the calculated number of each element, δ (atomic %), which is the total amount of metal elements excluding Li and element X, is calculated.

[0050] In addition, for Li, Ni, element M (described later), element X, carbon atoms, and oxygen atoms that may be present on the surface of the CAM, photoelectrons corresponding to the binding energy of each element are detected in the above-mentioned XPS analysis.

[0051] The peaks corresponding to each element can be identified using an existing database.

[0052] For example, the integral value of the Li1s waveform is used as the photoelectron intensity of Li.

[0053] The photoelectron intensities of Ni, Co, Mn, and Al are calculated by integral values ​​of the waveforms of Ni2p3 / 2, Co2p3 / 2, Mn2p1 / 2, and Al2p, respectively.

[0054] The P and B photoelectron intensities are calculated by integral values ​​of the P2p and B1s waveforms, respectively.

[0055] The integral value of the C1s waveform is used as the photoelectron intensity of the carbon atom.

[0056] The integral value of the O1s waveform is used as the photoelectron intensity of oxygen atoms.

[0057] [Method of measuring β] The above "ICP optical emission spectroscopy" is abbreviated as "ICP." ICP allows the amounts of elements present in the CAM to be analyzed.

[0058] First, several tens of milligrams of CAM powder is dissolved in acid or alkali at a ratio such that the element concentration in the solution is on the order of ppm. After that, the powder is analyzed using an ICP optical emission spectrometer.

[0059] As an ICP emission spectroscopic analyzer, for example, SPS3000 manufactured by SII NanoTechnology Inc. can be used.

[0060] From the amount of each metal element in the CAM obtained by ICP measurement, the content ratio β (unit: mol%) of element X relative to the total amount of each metal element excluding Li (100 mol%) is calculated.

[0061] Calculate α / β from α and β obtained by the above method.

[0062] (1) The ratio α / β is preferably 0.15 or more, and more preferably 0.3 or more, and is preferably 3.0 or less, and more preferably 2.5 or less. The CAM preferably satisfies the following (1)-1, and more preferably satisfies the following (1)-2. 0.15≦[α / β]≦3.0 (1)-1 0.3≦[α / β]≦2.5 (1)-2

[0063] In the CAM in which the value of α / β satisfies the above (1) and is preferably equal to or greater than the above lower limit, the compound containing the element X present in an appropriate amount on the surface of the secondary particles removes hydrogen fluoride present in the electrolyte, making the electrolyte less susceptible to deterioration, and as a result, the cycle characteristics of the lithium secondary battery are improved. In the CAM in which the value of α / β satisfies the above (1) and is preferably equal to or less than the above upper limit, the compound containing element X is present on the surface of the secondary particles to such an extent that it does not form a resistance layer, and therefore high charge / discharge capacity is easily achieved, which tends to improve the cycle characteristics of the lithium secondary battery.

[0064] is greater than 0 atomic %, preferably 0.1 atomic % or more, and more preferably 0.25 atomic % or more, and is preferably 5.0 atomic % or less, and more preferably 3.0 atomic % or less. α is preferably greater than 0 and equal to or less than 5.0 atomic %, more preferably 0.1-3.0 atomic %, and even more preferably 0.25-3.0 atomic %.

[0065] In the CAM having α equal to or greater than the lower limit, the compound containing element X present on the particle surface in an appropriate amount removes hydrogen fluoride present in the electrolyte, making the electrolyte less susceptible to deterioration, and as a result, the cycle characteristics of the lithium secondary battery are improved. In the CAM having an α value equal to or less than the upper limit, the compound containing the element X is present on the surface of the secondary particles to such an extent that it does not form a resistive layer, and therefore high charge / discharge capacity is easily achieved, which tends to improve the cycle characteristics of the lithium secondary battery.

[0066] (2) γ indicates the proportion of carbon atoms present on the surface of the CAM. The carbon atoms are derived from, for example, compounds having carbon atoms. Examples of compounds having carbon atoms include lithium carbonate, lithium hydrogen carbonate, and organic lithium compounds. In addition to these, compounds included are compounds contained in the raw materials used in the production of CAM, or compounds obtained by reaction of the raw materials in the production of CAM.

[0067] A CAM that satisfies the above condition (2) contains fewer compounds that contain carbon atoms that can become resistance components, and therefore the charge / discharge efficiency of the produced battery is improved, and the cycle characteristics are likely to be improved.

[0068] It is more preferable that γ is 0 to 8.8 atomic %. γ may be more than 0 atomic % and less than 9.0 atomic %, or more than 0 atomic % and 8.8 atomic % or less. When γ is equal to or less than the upper limit, it means that the carbon atom-containing compound is not excessively formed in the surface region of the CAM, and since such a CAM has a small amount of resistance components, the charge / discharge efficiency is improved and the cycle characteristics are likely to be improved. Furthermore, when the compound containing carbon atoms is lithium carbonate, lithium carbonate produces water as a by-product when it reacts with hydrogen fluoride. When γ is equal to or less than the upper limit, the reaction that produces water as a by-product is less likely to occur, and deterioration of cycle characteristics can be suppressed.

[0069] For the above reasons, a CAM in which a compound containing element X is present on the surface and inside of a secondary particle and satisfies (1) and (2) can provide a lithium secondary battery with excellent cycle characteristics.

[0070] (3) It is preferable that the CAM satisfies the following (3). 0<(α / δ)×100≦50 (3) (In (3), δ is the total amount (atomic %) of metal elements other than Li and element X on the surface of the CAM, as measured by X-ray photoelectron spectroscopy.)

[0071] For the CAM, "(α / δ)×100" is preferably 25 or less, more preferably 20 or less, still more preferably less than 18, and "(α / δ)×100" is preferably 1 or more. (α / δ)×100 preferably satisfies the following (3)-1, more preferably satisfies (3)-2, still more preferably satisfies the following (3)-3, and particularly preferably satisfies the following (3)-4. 0 < (α / δ)×100 ≤ 25 (3)-1 0 < (α / δ)×100 ≤ 20 (3)-2 1 ≤ (α / δ)×100 ≤ 20 (3)-3 1 ≤ (α / δ)×100 < 18 (3)-4

[0072] "(α / δ)×100" is the abundance ratio of element X to the total amount of metal elements excluding Li on the surface of the CAM. When the abundance ratio of element X is below the above upper limit value, the exposure degree of LiMO on the surface of the CAM increases, and the insertion and desorption of lithium ions proceed smoothly. As a result, the resistance becomes low, and the cycle characteristics can be improved by the effect of removing hydrogen fluoride by the compound containing element X. When the abundance ratio of element X is above the above lower limit value, since some element X-containing compounds are present on the CAM surface, it becomes possible to prevent the deterioration of the CAM surface when it comes into contact with the electrolyte. As a result, the deterioration of the cycle characteristics can be suppressed.

[0073] [Composition formula] The CAM preferably contains Li, Ni, and element X, and more preferably contains Li, Ni, element X, and element M. Element M is one or more elements selected from the group consisting of Co, Mn, Fe, Cu, Ti, Mg, Al, W, Mo, Nb, Zn, Sn, Zr, Ga, and V. The CAM preferably satisfies the following formula (R). Li:Ni:M:X = (1 + x):y:z:a ···(R) (In formula (R), M is the above element M, X is the above element X, -0.1 ≤ x ≤ 0.2, 0 < y ≤ 0.95, 0 < z ≤ 0.95, 0 < a < 0.05, and y + z + a = 1.)

[0074] x is preferably −0.05 or more, and more preferably −0.02 or more. From the viewpoint of obtaining a lithium secondary battery having excellent cycle characteristics, x is preferably 0.1 or less, more preferably 0.08 or less, and even more preferably 0.06 or less.

[0075] The upper limit and lower limit of x can be combined in any way, for example, x can be −0.05 to 0.1, −0.05 to 0.08, or −0.02 to 0.06.

[0076] From the viewpoint of obtaining a lithium secondary battery having excellent cycle characteristics, y is preferably 0.3 or more, more preferably 0.5 or more, and is preferably 0.94 or less.

[0077] The upper limit and lower limit of y can be arbitrarily combined. Examples of combinations of y include more than 0 and 0.94 or less, 0.3 to 0.95, 0.3 to 0.94, and 0.5 to 0.94.

[0078] From the viewpoint of obtaining a lithium secondary battery having excellent cycle characteristics, z is preferably 0.005 or more.Z is preferably 0.7 or less, more preferably 0.5 or less, and even more preferably 0.4 or less.

[0079] The upper and lower limit values ​​of z can be arbitrarily combined. Examples of combinations of z include more than 0 and not more than 0.7, more than 0 and not more than 0.5, more than 0 and not more than 0.4, 0.005 to 0.7, 0.005 to 0.5, and 0.005 to 0.4.

[0080] a is preferably 0.005 or more. a is preferably 0.04 or less, and more preferably 0.01 or less. a is preferably 0.005 to 0.04, and more preferably 0.005 to 0.01.

[0081] The composition of the CAM can be determined from the ICP measurement results obtained by the above [Method of Measuring β].

[0082] The BET specific surface area of ​​CAM is 0.1 m 2 / g or more, and 0.2m 2 / g or more is more preferable, and 0.3m 2 It is more preferable that the BET specific surface area is 1.5 m 2 / g or less, and 1.4m 2 / g or less is more preferable, and 1.2m 2 It is more preferable that the molecular weight is not more than 1 / g.

[0083] BET specific surface area is 0.1-1.5m 2 / g is preferred, 0.2-1.4m 2 / g is more preferable, 0.3-1.2m 2 / g is more preferred.

[0084] When CAM having a BET specific surface area of ​​at least the lower limit is used, the reaction interface of the CAM increases, making it easier for lithium ions to enter and exit, and therefore the discharge capacity tends to increase, and as a result, the cycle characteristics tend to improve. When the CAM having a BET specific surface area of ​​not more than the upper limit is used, the contact area between the CAM and the electrolyte is less likely to increase, and hydrogen fluoride is less likely to be formed due to decomposition of the electrolyte, which can suppress deterioration of cycle characteristics.

[0085] [Measurement of BET specific surface area] The BET specific surface area of ​​CAM can be measured by a BET specific surface area measuring device. For example, Macsorb (registered trademark) manufactured by Mountech Co., Ltd. can be used as the BET specific surface area measuring device. When measuring powdered CAM, it is preferable to dry it in a nitrogen atmosphere at 105° C. for 30 minutes as a pretreatment.

[0086] [Method for measuring average crystallite size] The average crystallite size of CAM is determined by analyzing the diffraction peaks obtained from powder X-ray diffraction using CuKα radiation by Rietveld analysis. Specifically, CAM powder is filled into a dedicated substrate, and measurements are performed using a CuKα radiation source under conditions of a diffraction angle 2θ=10-90° and a sampling width of 0.02° to obtain a powder X-ray diffraction pattern. The diffraction peaks in the obtained powder X-ray diffraction pattern are subjected to Rietveld analysis to determine the crystallite size. For the Rietveld analysis, for example, TOPAS manufactured by Bruker can be used.

[0087] From the viewpoint of obtaining a lithium secondary battery having excellent cycle characteristics, the average crystallite size is preferably 50 nm or more, more preferably 55 nm or more, and even more preferably more than 57 nm, and is preferably 150 nm or less, and more preferably 120 nm or less. The average crystallite size is preferably 50-150 nm, more preferably 55-120 nm, and even more preferably greater than 57 nm and equal to or less than 120 nm.

[0088] When CAM having an average crystallite size of not less than the lower limit is used, the insertion and desorption of lithium ions can proceed smoothly, so that a lithium secondary battery having a high discharge capacity and excellent cycle characteristics can be obtained. When CAM having an average crystallite size of not more than the upper limit is used, deterioration due to particle cracking is unlikely to occur, so that a lithium secondary battery having excellent cycle characteristics can be obtained.

[0089] [LiMO] LiMO preferably contains at least Li, Ni and the above element M. Moreover, LiMO preferably contains at least Li, Ni, and an element M1, where the element M1 is one or more elements selected from the group consisting of Co, Mn, and Al.

[0090] LiMO has a layered structure, and preferably has a hexagonal crystal structure or a monoclinic crystal structure.

[0091] The hexagonal crystal structure belongs to any one space group selected from the group consisting of P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P62, P64, P63, P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P63 / mcm, and P63 / mmc.

[0092] In addition, the monoclinic crystal structure belongs to any one space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c, and C2 / c.

[0093] From the viewpoint of obtaining a lithium secondary battery with excellent cycle characteristics, LiMO preferably has a hexagonal crystal structure belonging to the space group R-3m or a monoclinic crystal structure belonging to the space group C2 / m.

[0094] [Method for confirming crystal structure] The crystal structure of LiMO can be confirmed by observing it using a powder X-ray diffractometer (for example, UltimaIV manufactured by Rigaku Corporation).

[0095] LiMO is preferably represented by the following compositional formula (I). Li (1+x) Ni y M z O2 (I) (In the compositional formula (I), M is the above element M, -0.1 ≤ x ≤ 0.2, 0 < y ≤ 0.95, 0 < z ≤ 0.95, and y + z = 1.)

[0096] The description of the preferable ranges of x, y and z in the compositional formula (I) is the same as the preferable ranges of x, y and z described in the formula (R).

[0097] <Method for manufacturing CAM> The method for manufacturing CAM is a method of sequentially performing the manufacturing process of MCC and the manufacturing process of CAM.

[0098] (Manufacturing process of MCC) MCC can be manufactured by the coprecipitation method. As the coprecipitation method, a batch coprecipitation method or a continuous coprecipitation method can be used. Hereinafter, the manufacturing method of MCC will be described in detail using, as an example, a metal composite hydroxide containing Ni as an essential element and element M as an optional element.

[0099] First, by the coprecipitation method, particularly the continuous coprecipitation method described in JP-A-2002-201028, a nickel salt solution, a metal salt solution of element M, and a complexing agent are reacted to produce a metal composite hydroxide represented by Ni y M z (OH)2 (where y + z = 1).

[0100] As the nickel salt which is the solute of the above nickel salt solution, for example, one or more of nickel sulfate, nickel nitrate, nickel chloride and nickel acetate can be used.

[0101] As the metal salt of element M which is the solute of the above metal salt solution of element M, for example, cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt acetate, manganese sulfate, manganese nitrate, manganese chloride, manganese acetate, aluminum sulfate, sodium aluminate, etc. can be used.

[0102] The above metal salts are used in amounts such that the molar ratio of Ni in the solute of the nickel salt solution and element M in the solute of the metal salt solution of element M becomes y:z corresponding to the composition ratio of Ni y M z (OH)2.

[0103] The solvent of the nickel salt solution and the metal salt solution of element M is water. That is, the nickel salt solution and the metal salt solution of element M are aqueous solutions.

[0104] The complexing agent is a compound capable of forming a complex in an aqueous solution with ions of Ni and element M. Examples include ammonium ion donors, hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracildiacetic acid, and glycine.

[0105] The amount of the complexing agent contained in the mixed liquid containing the nickel salt solution, the metal salt solution of element M, and the complexing agent is, for example, in a molar ratio greater than 0 and less than or equal to 2 relative to the total number of moles of the metal salts.

[0106] In the coprecipitation method, in order to adjust the pH value of the mixture, an aqueous solution of an alkali metal hydroxide, such as sodium hydroxide or potassium hydroxide, is added to the mixture before the pH of the mixture becomes neutral from alkaline.

[0107] In this specification, the pH value is defined as the value measured when the temperature of the mixed liquid is 40° C. The pH of the mixed liquid is measured when the temperature of the mixed liquid sampled from the reaction tank reaches 40° C.

[0108] When the nickel salt solution, the metal salt solution of element M, and a complexing agent are continuously supplied to the reaction vessel, Ni and element M react to produce Ni. y M z (OH)2 is produced.

[0109] During the reaction, the temperature of the reaction vessel is controlled preferably within the range of 20-80° C., more preferably within the range of 30-70° C. The pH value in the reaction vessel is controlled preferably within the range of 9-13, more preferably within the range of 11-13.

[0110] The materials in the reaction vessel are mixed by suitable stirring. The reaction vessel used in the continuous coprecipitation method may be a reaction vessel in which the formed reaction precipitate is allowed to overflow for separation.

[0111] In addition to controlling the above conditions, various gases, for example, inert gases such as nitrogen, argon, carbon dioxide, etc., air, oxidizing gases such as oxygen, etc., or a mixture thereof, may be supplied into the reaction vessel.

[0112] After the above reaction, the resulting reaction precipitate is washed, dehydrated and dried to obtain MCC.

[0113] In the above example, a metal composite hydroxide is produced as MCC, but a metal composite oxide may also be prepared.

[0114] The metal composite oxide can be prepared by oxidizing the metal composite hydroxide. The maximum temperature during oxidation is preferably 300-800° C. The oxidation time, which is the total time from the start of temperature increase to the end of temperature retention after reaching the temperature, is preferably 1-30 hours.

[0115] In this specification, the maximum holding temperature refers to the maximum holding temperature of the atmosphere in the furnace used during oxidation or calcination. When the oxidation or calcination process has multiple stages, the maximum holding temperature refers to the temperature at the stage that is carried out at the highest temperature among the stages.

[0116] The drying conditions for MCC are not particularly limited. The drying atmosphere may be an inert gas such as nitrogen, helium, or argon, or oxygen or air.

[0117] During drying, a reducing agent such as hydrazine or sodium sulfite may be used under an inert gas atmosphere.

[0118] After drying, the MCC may be classified as appropriate.

[0119] (CAM manufacturing process) The process for producing CAM includes step A of mixing MCC with a raw material containing element X to obtain a mixture, and step B of mixing the obtained mixture with a lithium compound and firing the mixture.

[0120] When the element X is P, the raw material containing the element X may be diammonium phosphate, lithium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium phosphate, or the like. When the element X is B, boric acid, lithium borate, trilithium borate, metaboric acid, etc. can be used.

[0121] MCC and the raw material containing element X are mixed in such a ratio that the amount (molar ratio) of element X contained in the raw material containing element X relative to the total amount of metal elements (Ni and element M) contained in MCC is preferably more than 0 and less than 0.05, more preferably 0.005 to 0.04, and even more preferably 0.005 to 0.02.

[0122] The method of mixing MCC with the raw material containing element X may be either a dry method or a wet method, but a wet method is preferred. By mixing MCC with the raw material containing element X by a wet method, element X is easily diffused inside the secondary particles. Therefore, it is easy to obtain CAM that satisfies the above (1) and has a compound containing element X on the surface and inside of the secondary particles.

[0123] When mixing by a wet method, it is preferable to prepare a solution of a raw material containing element X and spray the solution onto MCC. Examples of the solvent in the solution of the raw material containing element X include alcohol and water. In this embodiment, it is preferable to use water.

[0124] The mixture is preferably dried. The drying conditions are not particularly limited, but it is preferable that the mixture is not oxidized or reduced. Examples of the drying conditions include the use of an inert gas such as nitrogen, helium, or argon, and drying under a vacuum atmosphere.

[0125] The drying conditions for the above mixture are, for example, a temperature of 100-150° C. and a time of 1-10 hours.

[0126] By mixing MCC and a raw material containing element X before step B, the raw material containing element X can penetrate into the interior of MCC and can be diffused not only on the surface but also inside the secondary particles of MCC. Furthermore, by drying the above mixture, the raw material containing element X that has penetrated into the interior of MCC is attached. For this reason, a CAM can be obtained that satisfies the above (1), has a compound containing element X present on the surface and inside of the secondary particles, preferably has α within the above range, and preferably satisfies the above (3). It is preferable to continuously dry the MCC and the raw material containing the element X after mixing them. By continuously carrying out the above operations, the internal diffusion effect of the element X can be enhanced.

[0127] The mixture is dried and then mixed with a lithium compound to obtain a Li-containing mixture.

[0128] The mixture and the lithium compound are used in such a ratio that the amount (molar ratio) of Li contained in the lithium compound relative to the total amount of metal elements (Ni and element M) contained in the mixture is preferably 0.90 to 1.12, more preferably 0.95 to 1.11, and even more preferably 0.98 to 1.06.

[0129] The lithium compound may be any one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium hydroxide hydrate, lithium oxide, lithium chloride, and lithium fluoride, or a mixture of two or more of these. Of these, lithium hydroxide and / or lithium hydroxide hydrate are preferred.

[0130] Next, the Li-containing mixture is fired to obtain a fired product.

[0131] By firing the Li-containing mixture, the MCC, the raw material containing element X, and the lithium compound react with each other, the primary particles grow, and the primary particles aggregate and sinter. As a result, secondary particles having grain boundaries are formed. Since element X is present on the surface and inside of MCC, it is also contained on the surface and inside of the secondary particles in the fired product.

[0132] In addition, by carrying out step B after step A, the compound containing carbon atoms contained in the MCC reacts with the raw material containing element X, and the carbon atoms are emitted as carbon dioxide. As a result, CAM that satisfies (2) is obtained.

[0133] For the firing, dry air, an oxygen atmosphere, an inert atmosphere, or a mixture of these gases may be used depending on the desired composition. In this embodiment, an oxygen atmosphere is preferred.

[0134] The firing may be a single firing or may include multiple firing steps. When multiple firing steps are performed, the step having the highest holding temperature is referred to as main firing, the step of firing at a lower temperature before main firing is referred to as pre-firing, and the step of firing at a lower temperature after main firing is referred to as post-firing.

[0135] From the viewpoints of controlling the LiMO particle growth and γ within the above-mentioned range, the firing temperature during the main firing is preferably 600° C. or higher, more preferably 650° C. or higher, and even more preferably 700° C. or higher. Moreover, from the viewpoints of preventing cracks from forming in the CAM particles and maintaining the particle strength, the firing temperature is preferably 1200° C. or lower, more preferably 1100° C. or lower, and even more preferably 1000° C. or lower.

[0136] The firing temperature during the main firing is preferably 600-1200°C, more preferably 650-1100°C, and even more preferably 700-1000°C. In this embodiment, when the main firing is performed at 600°C or higher, it is easy to obtain CAM that satisfies the above formula (R) and preferably has a BET specific surface area and average crystallite size in the above-mentioned range. The higher the firing temperature, the smaller the BET specific surface area of ​​the CAM and the larger the average crystallite size.

[0137] The firing temperature in the pre-firing or post-firing may be lower than the firing temperature in the main firing. For example, the firing temperature may be in the range of 200-800°C. The firing temperature in the pre-firing is preferably 400-800°C, more preferably 450-700°C. The firing temperature in the post-firing is preferably 200-600°C, more preferably 300-500°C.

[0138] In the pre-firing, main firing, or post-firing, the holding time at each firing temperature is 0.1 to 20 hours, preferably 0.5 to 10 hours. The rate of temperature increase to the holding temperature is preferably 50 to 400° C. / hour, and the rate of temperature decrease from the holding temperature to room temperature is preferably 10 to 400° C. / hour.

[0139] The rate of temperature rise in this specification is calculated from the time from the start of temperature rise to the time when the highest temperature is reached and the temperature difference from the temperature at the start of temperature rise in the firing furnace to the highest temperature.

[0140] After firing, the resulting fired product may be crushed, which reduces the proportion of agglomerates of secondary particles and allows the production of CAM that is more likely to come into contact with the electrolyte.

[0141] The fired product may also be washed with a washing solution such as pure water or an alkaline washing solution. Examples of the alkaline washing solution include an aqueous solution of one or more anhydrides selected from the group consisting of LiOH (lithium hydroxide), NaOH (sodium hydroxide), KOH (potassium hydroxide), Li2CO3 (lithium carbonate), Na2CO3 (sodium carbonate), K2CO3 (potassium carbonate) and (NH4)2CO3 (ammonium carbonate), as well as an aqueous solution of a hydrate of the anhydrides. Ammonia water may also be used as the alkaline washing solution.

[0142] In the washing step, the method of contacting the fired product with the washing liquid may include a method in which the fired product is put into each washing liquid and stirred, a method in which each washing liquid is used as shower water and poured onto the fired product, or a method in which the fired product is put into the washing liquids and stirred, and then the fired product is separated from each washing liquid, and then each washing liquid is used as shower water and poured onto the separated fired product.

[0143] The temperature of the cleaning solution used for washing is preferably 15° C. or less, more preferably 10° C. or less, and even more preferably 8° C. or less. By controlling the temperature of the cleaning solution within the above range and at a temperature at which the cleaning solution does not freeze, excessive elution of lithium ions from the crystal structure of the fired material into the cleaning solution during washing can be suppressed.

[0144] The baked product after washing may be dried appropriately.

[0145] Through the above steps, the CAM is obtained.

[0146] <Lithium secondary battery> A positive electrode for a lithium secondary battery suitable for use with the CAM of this embodiment will be described below. Hereinafter, the positive electrode for a lithium secondary battery may be referred to as a positive electrode. Furthermore, a lithium secondary battery suitable for use as a positive electrode will be described.

[0147] An example of a suitable lithium secondary battery for use with the CAM of this embodiment has a positive electrode, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte solution disposed between the positive electrode and the negative electrode.

[0148] 1 is a schematic diagram showing an example of a lithium secondary battery. For example, a cylindrical lithium secondary battery 10 is manufactured as follows.

[0149] First, as shown in the partially enlarged view of FIG. 1 , a pair of belt-shaped separators 1, a belt-shaped positive electrode 2 having a positive electrode lead 21 at one end, and a belt-shaped negative electrode 3 having a negative electrode lead 31 at one end are laminated in the order of separator 1, positive electrode 2, separator 1, and negative electrode 3, and then wound to form an electrode group 4.

[0150] The positive electrode 2, for example, has a positive electrode active material layer 2a containing CAM, and a positive electrode current collector 2b on one surface of which the positive electrode active material layer 2a is formed. Such a positive electrode 2 can be manufactured by first preparing a positive electrode mixture containing CAM, a conductive material, and a binder, and supporting the positive electrode mixture on one surface of the positive electrode current collector 2b to form the positive electrode active material layer 2a.

[0151] Examples of the negative electrode 3 include an electrode in which a negative electrode mixture containing a negative electrode active material (not shown) is supported on a negative electrode current collector, and an electrode made of only the negative electrode active material. The negative electrode 3 can be manufactured in a manner similar to that for the positive electrode 2.

[0152] Next, the electrode group 4 and an insulator (not shown) are housed in the battery can 5, the bottom of the can is sealed, the electrode group 4 is impregnated with an electrolyte solution 6, and the electrolyte is disposed between the positive electrode 2 and the negative electrode 3. Furthermore, the upper part of the battery can 5 is sealed with a top insulator 7 and a sealing body 8, whereby a lithium secondary battery 10 can be manufactured.

[0153] The shape of the electrode group 4 can be, for example, a columnar shape such that the cross-sectional shape when the electrode group 4 is cut perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.

[0154] The shape of a lithium secondary battery having such an electrode group 4 may be any shape specified by IEC60086, a standard for batteries established by the International Electrotechnical Commission (IEC), or JIS C 800. For example, cylindrical or rectangular shapes may be used.

[0155] Furthermore, the lithium secondary battery is not limited to the above-mentioned wound type configuration, and may be a laminated type configuration in which a laminated structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of the laminated type lithium secondary battery include a so-called coin type battery, a button type battery, and a paper type (or sheet type) battery.

[0156] For the positive electrode, separator, negative electrode, and electrolyte constituting the lithium secondary battery, for example, the configurations, materials, and manufacturing methods described in

[0113] to

[0140] of WO2022 / 113904A1 can be used.

[0157] <All-solid-state lithium secondary battery> The CAM of this embodiment can be used as a CAM for an all-solid-state lithium secondary battery.

[0158] Fig. 2 is a schematic diagram showing an example of an all-solid-state lithium secondary battery. The all-solid-state lithium secondary battery 1000 shown in Fig. 2 has a laminate 100 having a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130, and an exterior body 200 that houses the laminate 100. The all-solid-state lithium secondary battery 1000 may also have a bipolar structure in which a CAM and a negative electrode active material are arranged on both sides of a current collector. A specific example of the bipolar structure is the structure described in JP-A-2004-9500.

[0159] The positive electrode 110 has a positive electrode active material layer 111 and a positive electrode current collector 112. The positive electrode active material layer 111 contains the above-mentioned CAM and a solid electrolyte. The positive electrode active material layer 111 may also contain a conductive material and a binder.

[0160] The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. The negative electrode active material layer 121 may also contain a solid electrolyte and a conductive material.

[0161] The laminate 100 may have an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 12. In addition, the all-solid-state lithium secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120.

[0162] The all-solid-state lithium secondary battery 1000 further includes an insulator (not shown) that insulates the laminate 100 from the exterior body 200 , and a sealing body (not shown) that seals the opening 200 a of the exterior body 200 .

[0163] A container molded from a highly corrosion-resistant metal material such as aluminum, stainless steel, or nickel-plated steel can be used as the exterior body 200. Also, a container formed into a bag shape from a laminate film having at least one surface treated to be corrosion-resistant can be used as the exterior body 200.

[0164] Examples of the shape of the all-solid-state lithium secondary battery 1000 include a coin type, a button type, a paper type (or a sheet type), a cylindrical type, a square type, and a laminate type (pouch type).

[0165] The all-solid-state lithium secondary battery 1000 is illustrated as having one laminate 100 as an example, but the present embodiment is not limited to this. The all-solid-state lithium secondary battery 1000 may have a configuration in which the laminate 100 is used as a unit cell, and a plurality of unit cells (laminated bodies 100) are sealed inside an exterior body 200.

[0166] For the all-solid-state lithium secondary battery, for example, the configuration, materials, and manufacturing method described in

[0151] to

[0181] of WO2022 / 113904A1 can be used.

[0167] In the lithium secondary battery having the above-mentioned configuration, since the CAM of this embodiment is used, a lithium secondary battery having excellent cycle characteristics can be provided.

[0168] Furthermore, since the positive electrode having the above-mentioned configuration has the CAM having the above-mentioned configuration, the cycle characteristics of the lithium secondary battery can be improved.

[0169] Furthermore, the lithium secondary battery having the above-mentioned structure has the above-mentioned positive electrode, and therefore is a secondary battery having excellent cycle characteristics.

[0170] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. EXAMPLES

[0171] <Measurement of α, γ, and δ> As described in the above [Measurement method of α, γ, and δ], α, γ, and δ of the CAM were measured.

[0172] <Measurement of β> As described in the above [Measurement method of β], β of the CAM was measured. Further, from the obtained measurement results, the composition ratio of the CAM was determined.

[0173] <Calculation of α / β> Using the values of α and β obtained by the above method, α / β, which is the ratio of α to β, was calculated.

[0174] <Calculation of “(α / δ)×100”> Using the values of α and δ obtained by the above method, “(α / δ)×100” was calculated.

[0175] <Presence or absence of element X inside the secondary particles> As described in the above [Analysis of the cross-section of secondary particles], the cross-section of the CAM was obtained, SEM-EDX analysis was performed, and the presence or absence of element X was evaluated.

[0176] <Measurement of BET specific surface area> As described in the above [Measurement of BET specific surface area], the BET specific surface area of the CAM was measured.

[0177] <Measurement of average crystallite size> As described in the above [Measurement method of average crystallite size], the average crystallite size of the CAM was calculated.

[0178] <Confirmation of crystal structure> As described in the above [Method for confirming crystal structure], the crystal structure of LiMO was confirmed.

[0179] <Evaluation of cycle characteristics> As described in the above [Measurement method of cycle retention rate], the cycle retention rate of the CAM was calculated and the cycle characteristics were evaluated.

[0180] <Example 1> (CAM1 manufacturing) Water was placed in a reaction vessel equipped with a stirrer and an overflow pipe, and then an aqueous solution of sodium hydroxide was added and the liquid temperature was maintained at 50°C.

[0181] A mixed raw material solution 1 was prepared by mixing an aqueous solution of nickel sulfate, an aqueous solution of cobalt sulfate, and an aqueous solution of manganese sulfate in such a ratio that the molar ratio of Ni, Co, and Mn was 0.6:0.2:0.2.

[0182] Next, in the reaction vessel, an aqueous solution of ammonium sulfate was continuously added as a complexing agent to the mixed raw material liquid 1 under stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times under the condition that the pH of the mixed liquid in the reaction vessel was 12.1 (when the liquid temperature was 40°C), and a reaction precipitate 1 was obtained.

[0183] The obtained reaction precipitate 1 was washed, dehydrated by a centrifuge, isolated, and dried at 105° C. for 20 hours to obtain a metal composite hydroxide, MCC1.

[0184] Diammonium hydrogen phosphate was weighed out so that the molar ratio of P to the total amount of Ni, Co, and Mn contained in MCC1 was P / (Ni+Co+Mn) = 0.011, and dissolved in 2.0 g of pure water to prepare aqueous solution 1.

[0185] The aqueous solution 1 obtained above was sprayed onto the MCC1 while mixing in a mortar to obtain a mixture 1.

[0186] The obtained mixture 1 was dried at 120° C. for 10 hours under a vacuum atmosphere.

[0187] Next, lithium hydroxide monohydrate powder was weighed out so that the molar ratio of Li to the total amount of Ni, Co, and Mn contained in mixture 1 was Li / (Ni+Co+Mn)=1.0. The lithium hydroxide monohydrate powder was mixed with mixture 1 to obtain Li-containing mixture 1.

[0188] The Li-containing mixture 1 was pre-fired in an oxygen atmosphere at 650° C. for 5 hours to obtain a pre-fired product 1.

[0189] The obtained pre-calcined product 1 was further calcined at 840° C. for 5 hours in an oxygen atmosphere to obtain CAM1.

[0190] (CAM1 evaluation) The LiMO contained in CAM1 had a layered structure. The composition ratio of CAM1 corresponding to the above formula (R) is shown in Table 1. In addition, the α, α / β, "(α / δ)×100", BET specific surface area, average crystallite size, and the presence or absence of element X inside the secondary particles of CAM1, as well as the cycle retention rate of the lithium secondary battery are shown in Table 2. The following examples and comparative examples are also similarly shown in Tables 1 and 2.

[0191] A cross-sectional photograph of CAM1 is shown in FIG. 3A, and the results of SEM-EDX analysis are shown in FIG. 3B. From Figures 3A and 3B, it was confirmed that P was present in a region (interior) of the secondary particle of CAM1 closer to the center of the particle than a position about 10 nm deep from the surface toward the center of the particle. Moreover, Figure 4A is a diagram in which a line indicated by an arrow symbol is added to the cross-sectional photograph of Figure 3A. The element spectrum of the range surrounded by the line indicated by the arrow symbol (in other words, the interior of the secondary particle) is shown in Figure 4B. A peak was observed at the position of P indicated by the arrow symbol in Figure 4B, confirming the presence of P inside the secondary particle.

[0192] <Example 2> (CAM2 Manufacturing) The calcined product 1 was calcined at 900°C for 5 hours in an oxygen atmosphere to obtain CAM 2. The LiMO contained in CAM 2 had a layered structure.

[0193] <Example 3> (CAM3 Manufacturing) Lithium dihydrogen phosphate was weighed out so that the molar ratio of P to the total amount of Ni, Co, and Mn contained in MCC1 was P / (Ni+Co+Mn) = 0.012, and dissolved in 2.0 g of pure water to prepare aqueous solution 3.

[0194] The aqueous solution 3 obtained above was sprayed onto the MCC1 while mixing them in a mortar to obtain a mixture 3.

[0195] CAM3 was obtained in the same manner as in Example 1, except that Mixture 3 was used. The LiMO contained in CAM3 had a layered structure.

[0196] <Example 4> (CAM4 Manufacturing) Boric acid was weighed out so that the molar ratio of B to the total amount of Ni, Co, and Mn contained in MCC1 was B / (Ni+Co+Mn)=0.011, and dissolved in 2.0 g of pure water to prepare aqueous solution 4.

[0197] The aqueous solution 4 obtained above was sprayed onto the MCC1 while mixing them in a mortar to obtain a mixture 4.

[0198] CAM4 was obtained in the same manner as in Example 1, except that Mixture 4 was used. The LiMO contained in CAM4 had a layered structure.

[0199] <Example 5> (CAM5 manufacturing) Water was placed in a reaction vessel equipped with a stirrer and an overflow pipe, and then an aqueous solution of sodium hydroxide was added and the liquid temperature was maintained at 50°C.

[0200] A mixed raw material solution 2 was prepared by mixing an aqueous nickel sulfate solution, an aqueous cobalt sulfate solution, and an aqueous manganese sulfate solution in a molar ratio of Ni, Co, and Mn of 0.85:0.05:0.10.

[0201] Next, in the reaction vessel, an aqueous solution of ammonium sulfate was continuously added as a complexing agent to the mixed raw material liquid 2 under stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times under the condition that the pH of the mixed liquid in the reaction vessel was 12.1 (when the liquid temperature was 40°C), and a reaction precipitate 2 was obtained.

[0202] The obtained reaction precipitate 2 was washed, dehydrated by a centrifuge, isolated, and dried at 105° C. for 20 hours to obtain a metal composite hydroxide, MCC5.

[0203] Diammonium hydrogen phosphate was weighed out so that the molar ratio of P to the total amount of Ni, Co, and Mn contained in MCC5 was P / (Ni+Co+Mn)=0.010, and dissolved in 2.0 g of pure water to prepare aqueous solution 5.

[0204] The aqueous solution 5 obtained above was sprayed onto the MCC 5 while mixing in a mortar to obtain a mixture 5.

[0205] The obtained mixture 5 was dried at 120° C. for 10 hours under a vacuum atmosphere.

[0206] Next, lithium hydroxide monohydrate powder was weighed out such that the molar ratio of Li to the total amount of Ni, Co, and Mn contained in mixture 5 was Li / (Ni+Co+Mn)=1.05. The lithium hydroxide monohydrate powder was mixed with mixture 5 to obtain Li-containing mixture 5.

[0207] The Li-containing mixture 5 was pre-fired in an oxygen atmosphere at 650° C. for 5 hours to obtain a pre-fired product 5.

[0208] The obtained pre-fired product 5 was further fired at 800° C. for 5 hours in an oxygen atmosphere to obtain a fired product 5, which was then crushed.

[0209] Pure water was added to the crushed fired product 5 in a weight ratio of 1:1, and the mixture was stirred with a stirrer for 20 minutes to obtain a washed fired product 5.

[0210] The washed fired product 5 was dried at 120° C. for 10 hours in a vacuum atmosphere to obtain CAM 5. The LiMO contained in CAM 5 had a layered structure.

[0211] <Comparative Example 1> (Manufacturing of CAM-C1) Lithium hydroxide monohydrate powder was weighed out in such a ratio that the molar ratio of Li to the total amount of Ni, Co, and Mn contained in MCC1 was Li / (Ni+Co+Mn) = 1.0. The lithium hydroxide monohydrate powder was mixed with MCC1 to obtain Li-containing mixture C1.

[0212] CAM-C1 was obtained in the same manner as in Example 1, except that the Li-containing mixture C1 was used. The LiMO contained in CAM-C1 had a layered structure.

[0213] <Comparative Example 2> (CAM-C2 manufacturing) Diammonium hydrogen phosphate was weighed out in such a ratio that the molar ratio of P to the total amount of Ni, Co, and Mn contained in CAM-C1 was P / (Ni+Co+Mn) = 0.021, and dissolved in 4.0 g of pure water to prepare aqueous solution C2.

[0214] The aqueous solution C2 obtained above was sprayed onto CAM-C1 while mixing in a mortar, and then dried at 120°C for 10 hours in a vacuum atmosphere to obtain CAM-C2. The LiMO contained in CAM-C2 had a layered structure.

[0215] <Comparative Example 3> (Manufacturing of CAM-C3) Diammonium hydrogen phosphate was weighed out so that the molar ratio of P to the total amount of Ni, Co, and Mn contained in CAM-C1 was P / (Ni+Co+Mn)=0.011. Diammonium hydrogen phosphate and CAM-C1 were mixed in a mortar to obtain CAM-C3. The LiMO contained in CAM-C3 had a layered structure.

[0216] A cross-sectional photograph of CAM-C3 is shown in Figure 5A. FIG. 5B is an element spectrum of the area enclosed by the dashed line in FIG. 5A (in other words, the inside of the secondary particle). No peak was observed at the position of P indicated by the arrow in FIG. 5B, and it was determined that no P was present inside the secondary particles.

[0217] <Comparative Example 4> (CAM-C4 manufacturing) Boric acid was weighed out so that the molar ratio of B to the total amount of Ni, Co, and Mn contained in CAM-C1 was B / (Ni+Co+Mn)=0.005. Lithium hydroxide monohydrate powder was weighed out so that the molar ratio of Li to B contained in boric acid was Li / B=3.0. Then, boric acid and lithium hydroxide monohydrate powder were dissolved in 462.2 g of pure water to prepare aqueous solution C4.

[0218] Using a tumbling fluidizer (Powrex Corporation, MP-01), the aqueous solution C4 was sprayed onto the CAM-C1 to obtain a mixture C4.

[0219] Then, the mixture C4 was calcined at 400° C. for 5 hours in an oxygen atmosphere to obtain CAM-C4. The LiMO contained in CAM-C4 had a layered structure.

[0220] (CAM-C5 manufacturing) <Comparative Example 5> The lithium hydroxide monohydrate powder was weighed out so that the molar ratio of Li to the total amount of Ni, Co, and Mn contained in MCC5 was Li / (Ni+Co+Mn)=1.05. The lithium hydroxide monohydrate powder and MCC5 were mixed to obtain a Li-containing mixture C5.

[0221] CAM-C5 was obtained in the same manner as in Example 5, except that the Li-containing mixture C5 was used. The LiMO contained in CAM-C5 had a layered structure.

[0222] [Table 1]

[0223] [Table 2]

[0224] The CAMs of Examples 1 to 3 and Comparative Examples 2 and 3 had Ni amounts of 55 mol% or more and less than 80 mol% relative to the total amount of metal elements excluding Li, and contained P as element X, while the CAM of Comparative Example 1 had Ni amounts of 55 mol% or more and less than 80 mol%. However, the CAM of Comparative Example 1 did not contain a compound containing P, and Comparative Examples 2 and 3 did not have a compound containing P inside the secondary particles, and did not satisfy (1) or (2). The CAMs of Examples 1 to 3 had superior cycle characteristics compared to Comparative Examples 1 to 3. The CAMs of Example 4 and Comparative Example 4 had Ni amounts of 55 mol % or more and less than 80 mol %, and contained B as element X. However, the CAM of Comparative Example 4 did not contain a compound containing B inside the secondary particles, and did not satisfy (1) and (2). The CAM of Example 4 had better cycle characteristics than Comparative Example 4.

[0225] The CAMs of Example 5 and Comparative Example 5 had an Ni amount of 80 mol % or more and contained P as the element X. However, the CAM of Comparative Example 5 did not contain a compound containing P. The CAM of Example 5 was superior in cycle characteristics to that of Comparative Example 5.

[0226] In the CAMs of Examples 1 to 5, a compound containing the element X was present in an appropriate amount on the surface, and a compound containing the element X was also present inside the secondary particles, so it is believed that the hydrogen fluoride produced could be removed without producing water as a by-product, and deterioration of the electrolyte due to a reaction between water and the electrolyte was unlikely to occur. In addition, in the CAMs of Examples 1 to 5, a compound containing carbon atoms was not formed in excess on the surface, so that it is believed that the resistance component was small and the cycle characteristics were improved. [Explanation of symbols]

[0227] 1: separator, 2: positive electrode, 2a: positive electrode active material layer, 2b: positive electrode current collector layer, 3: negative electrode, 4: electrode group, 5: battery can, 6: electrolyte, 7: top insulator, 8: sealing body, 10: lithium secondary battery, 21: positive electrode lead, 31: negative electrode lead, 100: laminate, 110: positive electrode, 111: positive electrode active material layer, 112: positive electrode current collector, 113: external terminal, 120: negative electrode, 121: negative electrode active material layer, 122: negative electrode current collector, 123: external terminal, 130: solid electrolyte layer, 200: exterior body, 200a: opening, 1000: all-solid-state lithium secondary battery

Claims

1. A positive electrode active material for a lithium secondary battery comprising: a lithium metal composite oxide having a layered structure; and a compound containing one or more elements X selected from the group consisting of P and B, wherein the lithium metal composite oxide contains secondary particles which are aggregates of primary particles, and the compound containing the element X is present on the surfaces and inside of the secondary particles, and the positive electrode active material for a lithium secondary battery satisfies the following (1) and (2): 0<[α/β]≦4.5 (1) 0atomic%≦γ≦9.0atomic% (2) (In (1), α is the abundance ratio (atomic %) of the element X relative to all elements on the surface of the positive electrode active material for a lithium secondary battery, as measured by X-ray photoelectron spectroscopy. β is the content ratio (mol %) of the element X relative to the total amount of metal elements excluding Li in the positive electrode active material for a lithium secondary battery, as measured by ICP emission spectroscopy. (2) In (2), γ is the abundance ratio (atomic %) of carbon atoms to all elements on the surface of the positive electrode active material for lithium secondary batteries, as measured by X-ray photoelectron spectroscopy.

2. The positive electrode active material for a lithium secondary battery according to claim 1 , wherein the positive electrode active material for a lithium secondary battery satisfies the following formula (R): Li:Ni:M:X=(1+x):y:z:a...Formula (R) (In formula (R), M is one or more elements selected from the group consisting of Co, Mn, Fe, Cu, Ti, Mg, Al, W, Mo, Nb, Zn, Sn, Zr, Ga, and V, and X is the element X, where -0.1≦x≦0.2, 0<y≦0.95, 0<z≦0.95, 0<a<0.05, and y+z+a=1.)

3. 3. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the α is greater than 0 atomic % and less than or equal to 5 atomic %.

4. The positive electrode active material for a lithium secondary battery according to claim 1 or 2, which satisfies the following (3): 0<(α / δ)×100≦50 (3) (In (3), δ is the total amount (atomic %) of metal elements other than Li and element X on the surface of the positive electrode active material for a lithium secondary battery, as measured by X-ray photoelectron spectroscopy.)

5. BET specific surface area is 0.1m 2 / g or more 1.5m 2 The positive electrode active material for a lithium secondary battery according to claim 1 or 2, wherein the Mo content is 1 / g or less.

6. 3. The positive electrode active material for a lithium secondary battery according to claim 1, having an average crystallite size of 50 nm or more and 150 nm or less.

7. A positive electrode for a lithium secondary battery comprising the positive electrode active material for a lithium secondary battery according to claim 1 or 2.

8. A lithium secondary battery comprising the positive electrode for lithium secondary batteries according to claim 7.

Citation Information

Patent Citations

  • Method for manufacturing a positive electrode active material for a lithium secondary battery and the positive electrode active material for a lithium secondary battery manufactured by the method

    JP2019512450A